Assembly and export determine the intracellular distribution of hepatitis B virus core protein subunits - Weigand, Kilian; Knaust, Andreas; Schaller, Heinz (Journal of general virology, 2010)
Little is known about the parameters and factors that determine the intracellular distribution of the hepatitis B virus core protein (HBc). In order to study HBc in living cells, HBc was tagged with green fluorescent protein (GFP). Being assembly-incompetent, the GFP-fusion protein was distributed equally throughout the cell. Mutational inactivation of known serine-phosphorylation sites within the C-terminal region led to predominantly intranuclear localization. Phosphorylation of these targets, presumably by an SR domain protein kinase, resulted in a predominantly cytoplasmic localization, which suggests active cytoplasmic export or retention. The phosphoserine itself, and not its negative charge, appears essential for the underlying mechanism. In addition, the arginine-rich, protamine-like domain surrounding these phosphorylation sites does not function as the dominant nuclear-localization signal, as had been assumed previously, because neither deleting nor altering these sequences led to a change in intracellular HBc subunit distribution. Restoring the capability of the fusion protein to form capsids by co-assembly with assembly-competent, sterically uncompromised HBc subunits provided a second assay that gave insight into the effects resulting from capsid formation. Assembly was found to be the dominant factor in the cytoplasmic retention of the GFP-HBc fusion protein. Furthermore, the stability of these empty capsids was influenced by the cell-cycle inhibitor nocodazole. Thus, the intracellular distribution of HBc is dominated by cytoplasmic assembly, which is supported by the active nuclear export of HBc subunits, and modulated during the cell cycle by the instability of capsids.